(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2021)
Research about noise mapping in University of PGRI Palembang area using Surfer 11 has been done on march 2021.Â Purposes of this research are to determine the noise level and mapping noise level using software golden surfer 11. Method purpossive sampling and metod of frequency distributionÂ are used on this research. So that the noise level Leq obtained. The results obtained indicate that at each measurement point the noise level has passed the quality standard limit except when the measurement is carried out in the morning. Parking zone and the main campus entrance are exceed the limits of noise levels and shown by contour maps.